Identitas Anak di Luar Nikah Menurut Permendagri No. 9 Tahun 2016 Tentang Percepatan Akta Kelahiran di Kabupaten Mojokerto - Satriya Jaya Wardana, Muhammad Said Agil; Putri, Putri; Wijaya, Moch. Syakroni Adi (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
This document examines the legal identity of children born out of wedlock through the perspectives of Islamic law, the Civil Code, and the regulations in Minister of Home Affairs Regulation No. 9 of 2016. The study uses a qualitative literature review approach to understand the legal challenges faced by children born out of wedlock in Indonesia. Under Islamic law, children born out of wedlock do not have a legal relationship with their biological fathers and only have a civil connection to their mothers. This impacts certain rights, such as inheritance, which are limited for these children. Data from the Population and Civil Registration Office (Dukcapil) in Mojokerto shows that in 2023, 362 children were recorded as born out of wedlock, highlighting the need for greater attention to legal recognition and protection of these children’s rights in both civil law and other areas. The study also highlights the important role of Regulation No. 9 of 2016, which aims to speed up the issuance of birth certificates for all children, including those born out of wedlock, as a progressive step toward ensuring their civil rights. With the rising number of children born out of wedlock, public awareness of children’s rights and the need for proper legal recognition should be continuously increased. This research seeks to provide a deeper understanding of the rights of children born out of wedlock, the legal challenges they face in obtaining fair legal recognition, and the importance of regulatory support to ensure their civil rights are fully protected.